Development and Analysis of Generalized Queuing Model - Agrawal, Sachin Kumar; Singh, B.K (International Journal of Computer Sciences and Engineering, 2025)
In the present work a generalized queuing model has been developed to investigate the various queuing characteristics in steady state. The model consists of two global servers having three servers each which are connected in tricum biserial way. The comprehensive governing equations has been given in mathematical formulation which has been used to find the various output parameters i.e., queue lengths, variances, joint probabilities, traffic intensities, average waiting time for customers. The present model is named a generalized queuing model because several models available in the literature can be developed as the special cases